Physical activity, screen time, and sleep quality of students during remote learning - Batista, Elias dos Santos; Bezerra, Helder Xavier; Maciel, Gabriel Pereira; Souza, Alesandra Araújo de; Castro, Marcela Rodrigues de; Filho, Valter Cordeiro Barbosa; Aniceto, Rodrigo Ramalho (O Mundo da Saúde, 2024)
The health and social crisis triggered by the coronavirus disease 2019 (COVID-19) pandemic significantly impacted society as a whole. In the educational context, social isolation and remote learning may have exacerbated unhealthy behaviors among high school students, such as excessive screen time and poor sleep quality. This study aimed to analyze the impact of remote learning and its consequences on students’ physical activity levels, accumulated screen time, and sleep quality. A cross-sectional study was conducted with 995 high school students, with a mean age of 22.34 ± 7.46, encompassing all 20 academic units of the Federal Institute of Rio Grande do Norte, Northeast Brazil. Data were collected between September 8 and November 29, 2021. An online questionnaire was structured, including recall information about behaviors before and during remote learning. Validated instruments were used to measure physical activity levels (IPAQ), exposure to recreational screen time, and sleep quality (MSQ). During remote learning, participants were more likely to be physically inactive (OR: 1.45, p-value<0.001), have more than two hours of screen time (OR: 1.77, p-value<0.001), and experience poorer sleep quality (OR: 1.68, p-value<0.001). These behavioral changes reflect the impact of adopting remote learning on students’ routines and health, highlighting the importance of social and educational organization with preventive approaches and interventions focused on health behaviors during public health challenges like this.